The effect of malachite green treatment on the hematological paramater of jade perch - Yaacob, Hasni Nabilah (2017)
Malachite green (MG) is extensively used as an antiprotozoal and antifungal agent in the aquaculture industry. Since MG is toxic, the present study was conducted to investigate the effect of MG on the hematological parameter of jade perch (Scortum barcoo). Sixty jade perch were divided into control and two treatment groups; one immersed in MG for bath at 0.5mg.l−1 daily changed for 5 days maintaining the same concentration and another treated for a single dip at 66.7 mg.l−1 for 30 seconds. For all groups, blood was collected on day 0, 1, 5, 7, 11, 13, 15, 19, and 21 for hematological parameters (RBC count, hemoglobin, PCV, MCV, MCHC, and WBC). Analysis of hematological parameter using T-test for dip treatment showed significant difference on PCV, MCHC and WBC while for bath treatment significant difference seen on PCV, RBC, MCHC, and WBC. However, there was no general trend seen in these changes. Fish given bath treatment showed reddening of pectoral and caudal fin, petechial hemorrhage on the body, erratic swimming and anorexia during exposure to MG. In conclusion, although there were some significant differences of hematological parameter there was no obvious general trend. However, the clinical signs seen in bath treatment indicate that the fish were under stress.